2017
DOI: 10.1080/00016489.2017.1393841
|View full text |Cite
|
Sign up to set email alerts
|

Cervical necrotizing fasciitis: an overlooked diagnosis of a fatal disease

Abstract: Maintaining a high index of suspicion is crucially important for diagnosing CNF. Early diagnosis, timely resuscitation, and aggressive surgical debridement are the key to a successful clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
8
0
6
Order By: Relevance
“…For the period 1987–2018 105 total papers were identified. After excluding duplicate studies, nonodontogenic cases, review articles, and studies without analyzable individual patient data, a total of 58 studies reporting 164 total patients were identified [ 1 , 7 63 ]. Case reports, case series, and cohort studies containing individual analyzable patient data on patients of any age with a pathologic diagnosis of odontogenic necrotizing fasciitis were included in the systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…For the period 1987–2018 105 total papers were identified. After excluding duplicate studies, nonodontogenic cases, review articles, and studies without analyzable individual patient data, a total of 58 studies reporting 164 total patients were identified [ 1 , 7 63 ]. Case reports, case series, and cohort studies containing individual analyzable patient data on patients of any age with a pathologic diagnosis of odontogenic necrotizing fasciitis were included in the systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…Cervical fasciitis (CF) is a group of bacterial infections, usually of odontogenic or amygdala origin, characterized by necrosis of the fascia and subcutaneous cellular tissue of the neck [1, 2]. It is a rare disease with high morbimortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Syok sepsis dapat diidentifikasi dengan adanya klinis sepsis dengan hipotensi menetap yang membutuhkan vasopressor untuk mempertahankan Mean Atrerial Pressure <65 mmHg dan kadar laktat serum >2 mmol/L (18 mg/dL). 2,4 Kriteria klinis pasien sepsis dapat diketahui dengan menggunakan skor Sequential Organ Failure Assessment (SOFA score). Diagnosis sepsis dapat ditegakkan apabila skor SOFA>2.…”
unclassified
“…Penyakit ini termasuk infeksi kulit dan jaringan lunak (skin and soft tissue infection -SSTI). 3,4 Kasus ini jarang ditemukan, hanya sekitar 500-1500 kasus FN yang dilaporkan di Amerika Serikat. 1 Data terkait kasus FN di Indonesia belum tersedia.…”
unclassified
See 1 more Smart Citation